Radiotherapy Improves the Survival of Patients With Metastatic Cervical Cancer: A Propensity-Matched Analysis of SEER Database. Issue 7 (1st September 2018) - Huang, Kejie; Jia, Mingfang; Li, Ping; Han, Jianglong; Zhang, Rui; Li, Qin; Qiao, Yunfeng; Xu, TangPeng; Ruan, Peng; Song, Qibin; Li, Yanbo; Fu, Zhenming
Abstract : Objective: To demonstrate whether radiotherapy has an effect on the survival of patients with stage IVb (M1) cervical cancer, as it has not been adequately clarified. Methods: We analyzed International Federation of Gynecology and Obstetrics (FIGO) stage M1 cervical cancer diagnosed in patients between 1992 and 2013 using population-based data from the Surveillance, Epidemiology, and End Results registry. Propensity score (PS) analysis with 1:1 matching and the nearest neighbor matching method was performed to ensure well-balanced characteristics of comparison groups. Data were analyzed by Kaplan-Meier and Cox proportional hazards regression models to evaluate the overall survival (OS) and cancer-specific survival (CSS) months with corresponding 95% confidence intervals (95% CIs). Results: In general, receiving radiotherapy significantly improved OS and CSS both before and after PS matching (PSM) ( P < 0.001), with significantly improved OS (hazard ratio, 0.69; 95% CI, 0.62-0.76) and CSS (hazard ratio, 0.79; 95% CI, 0.70-0.89) after PSM in patients with stage M1 cervical cancer. Before PSM, radiotherapy was found to be associated with improved survival even for the patients with stage M1 cervical cancer with extensive metastasis (≥2 metastatic sites) ( P < 0.001). Although P value was not significant for brain metastasis, the survival month was numerically improved before PSM (OS and CSS, 1 month vs 4 months). Overall, radiotherapy still significantly improved survival for patients with one metastatic site (ie, oligometastases) either before or after PSM ( P < 0.05), with the survival month improved more than 6 months. Conclusions: The large Surveillance, Epidemiology, and End Results results support that radiotherapy might improve the survival of patients with metastatic cervical cancer. It might be prudent to carefully select suitable patients for radiation therapy for metastatic cervical cancer.